Acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface for the diagnosis of compensated liver cirrhosis - Pfeifer, Lukas; Görtz, Rüdiger; Sturm, Jörg; Wachter, David; Riener, M. O.; Schwitulla, Judith; Bernatik, T.; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2014)
To evaluate the diagnostic value of acoustic radiation force impulse (ARFI) and high-frequency ultrasound of the liver surface, using histology as a gold standard for the diagnosis of compensated liver cirrhosis.73 patients without ascites undergoing liver biopsy were included in the study. The left and right liver lobes were examined with ARFI and high-frequency ultrasound. Liver surface irregularity was quantified using image analysis software to calculate the difference between the real surface and the approximated physiological surface through a 20 mm standardized line.There is a significant difference between cirrhotic and non-cirrhotic patients for both quantified liver surface (QLS) and ARFI (p < 0.001). The mean values for QLS of the left lobe were 0.71 ± 0.24 mm and 1.17 ± 0.80 mm, of the right lobe 0.56 ± 0.26 mm and 0.87 ± 0.26 mm for non-cirrhotic and cirrhotic patients, respectively. The mean values of ARFI measurements of the left lobe were 2.04 ± 0.76 m/s and 2.85 ± 0.81 m/s, of the right lobe 1.65 ± 0.61 m/s and 3.02 ± 0.77 m/s for non-cirrhotic and cirrhotic patients, respectively. Diagnostic accuracy (AUROC) was 0.78/0.80 for QLS and 0.77/0.91 for ARFI of the left/right lobe, respectively. ARFI of the right lobe is significantly better than ARFI of the left (p = 0.023) or QLS of the left (p = 0.025)/right (p = 0.046) lobe of the liver.Assessment of liver surface irregularity by high-frequency ultrasound (QLS) is a useful diagnostic test for the assessment of compensated liver cirrhosis. ARFI of the right liver lobe is significantly better than high-frequency ultrasound (QLS of the left/right lobe of the liver) and ARFI of the left lobe of the liver.
EVALuna2:1858

Analysis of GDF15 and IGFBP7 in Hyperemesis Gravidarum Support Causality - Fejzo, Marlena S.; Fasching, Peter; Schneider, Michael; Schwitulla, Judith; Beckmann, Matthias; Schwenke, Eva; Macgibbon, Kimber W.; Mullin, Patrick M. (Geburtshilfe und Frauenheilkunde, 2019)
Objective Hyperemesis gravidarum, severe nausea and vomiting in pregnancy, occurs in up to 2% of pregnancies and leads to significant weight loss, dehydration, electrolyte imbalance, and ketonuria. It is associated with both maternal and fetal morbidity. Familial aggregation studies and twin studies suggest a genetic component. In a recent GWAS, we showed that placentation, appetite, and cachexia genes GDF15 and IGFBP7 are linked to hyperemesis gravidarum (HG). The purpose of this study is to determine whether GDF15 and IGFBP7 are upregulated in HG patients. Methods We compared serum levels of GDF15 and IGFBP7 at 12 and 24 weeks' gestation in women hospitalized for HG, and two control groups, women with nausea and vomiting of pregnancy (NVP), and women with no NVP. Results We show GDF15 and IGFBP7 serum levels are significantly increased in women with HG at 12 weeks' gestation. Serum levels of hCG are not significantly different between cases and controls. At 24 weeks gestation, when symptoms have largely resolved, there is no difference in GDF15 and IGFBP7 serum levels between cases and controls. Conclusion This study supports GDF15 and IGFBP7 in the pathogenesis of HG and may be useful for prediction and diagnosis. The GDF15-GFRAL brainstem-activated pathway was recently identified and therapies to treat conditions of abnormal appetite are under intense investigation. Based on our findings, HG should be included.
CRIS-Team Scopus Importer:2019-05-02
Keywords: GDF15; GFRAL; hyperemesis gravidarum; IGFBP7; nausea and vomiting of pregnancy

Aortic Arch Reconstruction in Neonates with Biventricular Morphology: Increased Risk for Development of Recoarctation by Use of Autologous Pericardium - Bechtold, Caroline; Purbojo, Ariawan; Schwitulla, Judith; Glöckler, Martin; Toka, Okan; Dittrich, Sven; Cesnjevar, Robert; Rüffer, André (Thoracic and Cardiovascular Surgeon, 2015)
Background The aim of this study was to analyze risk factors promoting development of recoarctation (Re-CoA) in neonates who survived aortic arch repair from an anterior approach. Methods Fifty consecutive neonates with biventricular morphology and ductal-dependent lower body perfusion who were discharged home following aortic arch repair with cardiopulmonary bypass between 2000 and 2012 were retrospectively reviewed. Arch anatomy was either interruption (n = 10) or hypoplasia with coarctation (n = 40). Aortic arch reconstruction was performed by using patch material (bovine pericardium, n = 30, homograft, n = 10, or glutaraldehyde-treated autologous pericardium, n = 7), and three patients underwent direct end-to-side anastomosis. Antegrade cerebral and continuous myocardial perfusion was performed in 39 and 21 patients, respectively. Kaplan-Meier freedom from Re-CoA was calculated. Morphologic and perioperative data indicating increased risk of Re-CoA by univariate analysis were included in multivariate Cox regression analysis. Results Mean follow-up was 5.3 ± 4.1 years. Re-CoA occurred in 13 patients and was treated successfully by balloon dilatation (n = 6) or surgery (n = 7). Freedom from Re-CoA after 1 and 5 years was 83 ± 5 and 79 ± 6%, respectively. Two patients died early after surgical repair of Re-CoA. The use of autologous pericardium for aortic arch augmentation was the only independent risk factor for development of Re-CoA (hazard ratio: 4.3 [95% confidence interval: 1.2-16.1]; p = 0.028). Conclusion Re-CoA following neonatal aortic arch surgery can be treated by balloon dilatation or surgery, if adequate. In this study, the risk for development of Re-CoA was independently increased by the use of autologous pericardium during initial arch repair.
EVALuna2:5488

Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
PURPOSE: Complementary medicine services are nowadays usually quite heterogeneous, and little information is available on standards for running an integrative medicine consultancy service. This study aimed to assess patients' satisfaction with a standardized treatment service on integrative medicine. METHODS: Using a cross-sectional design, 75 breast cancer patients from the integrative medicine consultancy service at the University Breast Center for Franconia were evaluated between January 2016 and March 2017. At primary consultation, patients answered a standardized questionnaire on their medical history and treatment goals regarding integrative medicine. In a subsequent interview, patients evaluated their satisfaction with the treatment service and individual treatment goals. RESULTS: 72% of the patients (n = 54) reported high satisfaction with the overall approach of the treatment service. 76% of the patients (n = 57) were very satisfied or satisfied with their individual treatment plans. The most frequently reported goals were to slow tumor progression (n = 64, 85.3%), reducing the side effects of conventional cancer treatments (n = 60, 80%), and a desire to participate actively in the treatment of breast cancer (n = 64, 85.3%). CONCLUSIONS: Using a standardized procedure in integrative medicine allows a high quality level to be offered to patients. Overall, breast cancer patients report very high satisfaction with the integrative medicine consultancy service and state long-term treatment goals. Hence, long-term treatment with integrative medicine methods should be taken into consideration.
EVALuna2:209947

Correction to: Breast cancer patients' satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service - Hack, Carolin; Antoniadis, Sophia; Hackl, Janina; Langemann, Hanna; Schwitulla, Judith; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Archives of Gynecology and Obstetrics, 2018)
In the original version of this article contained an error in figure 1. It was provided in German.
EVALuna2:209949

Correlation of the tibial tuberosity-trochlear groove distance with the Q-angle - Dickschas, Joerg; Harrer, Joerg; Bayer, Thomas; Schwitulla, Judith; Strecker, Wolf (Knee Surgery Sports Traumatology Arthroscopy, 2016)
The Q-angle has been used for years to quantify lateralization of the patella. The tibial tuberosity-trochlea groove distance (TT-TG distance) was introduced to analyse patellar tracking. Does a significant correlation exist between these two parameters? Do other significant interrelations exist between the Q-angle/TT-TG distance, torsion of the femur and tibia, the frontal axis, overall leg length, gender, former patellar dislocation, BMI?One hundred knees in 55 patients with patellofemoral symptoms were included in a prospective study. All patients underwent clinical examination, including measurement of the Q-angle. A torsional CT was obtained from all patients.The correlation coefficient was 0.33/0.34 (left/right leg), showing that the TT-TG distance tends to rise in direct ratio to a rising Q-angle. Thus, a significant correlation was found (p = 0.017). Femoral and tibial torsion had a positive effect on the TT-TG distance, but showed no significant correlation. Leg length had a significant effect on the TT-TG distance (p = 0.04). The frontal axis had a nonsignificant influence on the Q-angle or TT-TG distance. On average, the Q-angle in women was 2.38° greater than it was in men, but the difference was not significant.A significant correlation was noted between the Q-angle and the TT-TG distance. Both depend on various parameters and must be assessed for the analysis of patellofemoral maltracking. The Q-angle did not differ significantly between men and women; thus, the conclusion is that no different ranges need not be used.Diagnostic study, Level III.
EVALuna2:5481

Genetic predictors of chemotherapy-related amenorrhea in women with breast cancer - Ruddy, Kathryn J.; Schaid, Daniel J.; Partridge, A. H.; Larson, Nicholas B.; Batzler, Anthony; Häberle, Lothar; Dittrich, Ralf; Widschwendter, P.; Fink, Visnja; Bauer, Emanuel; Schwitulla, Judith; Rübner, Matthias; et al. (Fertility and Sterility, 2019)
Objective: To study how genetics may play a role in determining risk of chemotherapy-related amenorrhea (CRA) in young women with breast cancer. Design: Genome-wide association study. Setting: Not applicable. Patient(s): Premenopausal women ≤45 years of age enrolled in one of these three trials were included if they had at least one menstrual case report form after chemotherapy ended and if they were of European ancestry. Forms during and up to 3 months after receipt of GnRH agonist were excluded. Intervention(s): None. Main Outcome Measure(s): The association of single-nucleotide polymorphisms with post-chemotherapy menstruation adjusted for trial and arm, age, tamoxifen use, and nodal status. Result(s): The median age of the 1,168 women was 41 years (range 19–45). Among these, 457 (39%) never resumed menses after chemotherapy. Older age, tamoxifen use, and node-negative disease were associated with increased risk of CRA. Adjusting for these, rs147451859, in an intron of PPCDC (phosphopantothenoylcysteine decarboxylase), and rs17587029, located 5′ upstream of RPS20P11 (ribosomal protein S20 pseudogene 11), were associated with post-chemotherapy menstruation. Conclusion(s): Genetic variation may contribute to risk of CRA. Better prediction of who will experience CRA may inform reproductive and treatment decision making in young women with cancer.
CRIS-Team Scopus Importer:2019-08-06
Keywords: amenorrhea; Breast neoplasms; drug therapy; toxicity

Genetic variants in the glucocorticoid pathway genes and birth weight - Schneider, Michael; Hübner, Theresa; Pretscher, Jutta; Goecke, Tamme W.; Schwitulla, Judith; Häberle, Lothar; Kornhuber, Johannes; Ekici, Arif Bülent; Beckmann, Matthias; Fasching, Peter; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: The aim of this study was to examine associations between single nucleotide polymorphisms (SNPs) that tag genetic variation in the glucocorticoid pathways (particularly in maternal genes FKBP5, NR3C1, and CRHR1) and birth weight. Methods: The Franconian Maternal Health Evaluation Study (FRAMES) recruited healthy pregnant women prospectively for the assessment of maternal and fetal health. Germline DNA was collected from 375 pregnant women. Nine SNPs in the above-mentioned genes were genotyped. After reconstruction of haplotypes for each gene, a linear regression model was applied to the data to describe the association between haplotypes and birth weight. Results: Female sex in the newborn (compared to male) was associated with lower birth weight, whereas a later week of gestation, higher body mass index pre-pregnancy, and higher parity were associated with higher birth weight. No association with birthweight was shown for the haplotypes of the selected SNPs. Conclusions: In this cohort of healthy unselected pregnant women, the analyzed candidate haplotypes in FKBP5, NR3C1, and CRHR1 did not show any association with birth weight. This might be in line with several other studies that have found no influence of fetal polymorphisms in the glucocorticoid receptor gene or triggers of the maternal HPA axis such as stress and psychosocial problems on birth weight. However, the small sample size in this study and the lack of consideration of individual risk factors and levels of stress in this cohort needs to be taken into account when interpreting the results.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Birth weight; CRHR1; FKBP5; NR3C1; Single nucleotide polymorphisms

Genetic variations in estrogen and progesterone pathway genes in preeclampsia patients and controls in Bavaria - Pretscher, Jutta; Rübner, Matthias; Ekici, Arif Bülent; Rödl, Melanie; Hübner, Hanna; Schwitulla, Judith; Titzmann, Adriana; Hartwig, Charlotte; Beckmann, Matthias; Fasching, Peter; Schneider, Michael; Schwenke, Eva (Archives of Gynecology and Obstetrics, 2020)
Purpose: Hypertensive pregnancy disorders and preeclampsia are major causes of maternal and fetal morbidity and mortality worldwide. Many different organs are involved in the diseases’ clinical phenotype. The underlying mechanism is still unknown, with a possible genetic component. This case–control study investigated effects on the risk of preeclampsia of genetic variations (single nucleotide polymorphisms, SNPs) in the estrogen and progesterone pathway genes. Methods: The study included 167 patients with preeclampsia and 115 healthy controls from the “Franconian Maternal Health Evaluation Studies” (FRAMES). All patients completed an epidemiological questionnaire, data from which were correlated with prospective data on pregnancy and labor. DNA was isolated from blood samples and genotyping was done by PCR. Variants in the aromatase gene CYP19A1 (rs10046, rs4646), progesterone receptor gene (rs1042838, rs10895068), and estrogen receptor-α gene (rs488133) were examined, and the genotype distribution in the two groups was analyzed statistically. Results: A significant difference in the distribution frequency of genotypes between preeclampsia patients and controls was identified in one of the five SNPs. For rs10895068 in the progesterone receptor gene, genotype G/A was significantly more frequent among cases than controls (P = 0.023). No significant differences between the two cohorts were found in the other SNPs. Conclusions: This study showed a significant association between only one SNP in the progesterone receptor and preeclampsia. Other studies have also noted genetic aspects of preeclampsia. The underlying mechanism and causal relationship are not yet known, and further research is needed to explain the extent of genetic variations and the causal relationship in preeclampsia.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Genetic marker; Preeclampsia; Pregnancy; Single nucleotide polymorphism (SNP)

Intensified pharmaceutical care is improving immunosuppressive medication adherence in kidney transplant recipients during the first post-transplant year: a quasi-experimental study - Joost, Robert; Dörje, Frank; Schwitulla, Judith; Eckardt, Kai-Uwe; Hugo, Christian (Nephrology Dialysis Transplantation, 2014)
Medication adherence is critical for transplant patients because the consequences of non-adherence can result in allograft loss and may be life threatening.A prospective study with 74 renal transplant recipients using a sequential control group design was performed to investigate the impact of a pharmaceutical intensified care programme led by a clinical pharmacist on daily drug adherence during the first year after renal transplantation. Thirty-nine patients of the control group received the already established standardized drug and transplant training, while 35 patients of the intensified care group (ICG) received additional inpatient and outpatient pharmaceutical care and counselling by a dedicated clinical pharmacist. Applied interventions were clustered and classified using the behaviour change technique taxonomy according to Michie. Adherence to immunosuppressive drug therapy was monitored up to 1 year using a medication event monitoring system, pill count (PC), drug holiday (DH) occurrence, Morisky questionnaire and self-report.Sixty-seven patients (35 of the standard care and 32 of the ICG) were analysed. Implementation of DA was significantly (P = 0.014) improved in patients of the ICG (91%) compared with SCG (75%) during the first year after transplantion. Daily adherence measures were already improved within 30-40 days after start of intensified patient care and continued throughout the study period. Intensified care patients also showed significantly better results for taking adherence (P = 0.006), PC (P = 0.008) and DHs (P = 0.001).The additional, intensified pharmaceutical care improved patients' medication adherence remarkably, suggesting that the applied additional care programme has the potential to improve outcomes after organ transplantation.
EVALuna2:3715

Multiple contact sensitization - Schwitulla, Judith; Uter, Wolfgang (Hautarzt, 2015)
Contact allergy to several non-related haptens, usually termed polysensitization (PS), is often used to characterize patients who are particularly prone to sensitization. A conventional definition for PS is positive reactions to three or more haptens of the baseline series, e.g., the baseline series of the German Contact Dermatitis Research Group. Previous genetic as well as epidemiological studies have already indicated a number of potential risk factors for PS. In this context, both endogenous as well as exogenousfactors appear to be crucial. The former comprise polymorphism of IL-16 and TNF coding genes, the latter mostly occupational exposure, which often entails intense and repeated skin contact to a set of more or less characteristic contact allergens. Moreover, age and sex are related both with contact allergy to certain substances and with PS, as is the anatomical site of contact dermatitis. The degree to which contact allergy to a specific hapten is associated with PS, i.e., with contact allergy to several other haptens, varies greatly.
EVALuna2:5530

Prospective Evaluation of Acoustic Radiation Force Impulse (ARFI) Elastography and High-Frequency B-Mode Ultrasound in Compensated Patients for the Diagnosis of Liver Fibrosis/Cirrhosis in Comparison to Mini-Laparoscopic Biopsy - Pfeifer, Lukas; Zopf, Steffen; Schwitulla, Judith; Wildner, Dane; Wachter, David; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (Ultraschall in der Medizin, 2015)
Purpose: Ultrasound is a well-established noninvasive test for assessing patients with liver disease. This study aims to prospectively compare ultrasound to the new technique elastography (ARFI) for the assessment of liver fibrosis/cirrhosis. Materials and Methods: High-frequency B-mode ultrasound (liver surface/vein irregularity, liver homogeneity, spleen size), ARFI quantification, mini-laparoscopic liver evaluation including biopsy were prospectively obtained in compensated patients scheduled for liver biopsy. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. Results: Out of 157 patients, 35 patients were diagnosed cirrhotic. Ultrasound (combination of liver vein and/or surface irregularity) showed no significant difference compared to ARFI quantification for the diagnosis of significant liver fibrosis (Ishak> = 3) and cirrhosis. Diagnosis of cirrhosis had a sensitivity/specificity/PPV/NPV of 83 %(± 12) / 82 %(± 7) / 57 %(± 14) / 94 %(± 4), respectively, with ultrasound and 86 %(± 12) / 81 %(± 7) / 57 %(± 13) / 95 %(± 4), respectively, with ARFI quantification. The sensitivity/specificity/PPV/NPV for the detection of significant fibrosis were 68 %(± 13) / 86 %(± 7) / 71 %(± 13) / 84 %(± 7), respectively, for ultrasound and 70 %(± 12) / 84 %(± 7) / 69 %(± 12) / 84 %(± 7), respectively, for ARFI quantification. Conclusion: ARFI elastography and high-frequency B-mode ultrasound show similar and good results for the diagnosis of compensated liver cirrhosis and high-grade fibrosis. A key benefit of both methods is the high NPV suggesting them as noninvasive exclusion tests.
EVALuna2:2049

RANKL and OPG and their influence on breast volume changes during pregnancy in healthy women - Wunderle, Marius; Rübner, Matthias; Häberle, Lothar; Schwenke, Eva; Hack, Carolin; Bayer, Christian M.; Koch, Martin; Schwitulla, Judith; Schulz-Wendtland, Rüdiger; Kozieradzki, Ivona; Lux, Michael P.; Beckmann, Matthias; et al. (Scientific Reports, 2020)
Breast cancer risk is reduced by number of pregnancies and breastfeeding duration, however studies of breast changes during or after pregnancy are rare. Breast volume changes - although not linked to breast cancer risk - might be an interesting phenotype in this context for correlative studies, as changes of breast volume vary between pregnant women. Serum receptor activator of nuclear factor kappa B ligand (RANKL) and its antagonist osteoprotegerin (OPG) were measured prospectively before gestational week 12, and three-dimensional breast volume assessments were performed. A linear regression model including breast volume at the start of pregnancy, RANKL, OPG, and other factors was used to predict breast volume at term. The mean breast volume was 413 mL at gestational week 12, increasing by a mean of 99 mL up to gestational week 40. In addition to body mass index and breast volume at the beginning of pregnancy, RANKL and OPG appeared to influence breast volume with a mean increase by 32 mL (P = 0.04) and a mean reduction by 27 mL (P = 0.04), respectively. Linking the RANKL/RANK/OPG pathway with breast volume changes supports further studies aiming at analysing breast changes during pregnancy with regard to breast cancer risk.
CRIS-Team Scopus Importer:2020-03-31

Self-reported Improvement in Side Effects and Quality of Life With Integrative Medicine in Breast Cancer Patients - Hack, Carolin; Hackl, Janina; Huettner, Nina B. M.; Langemann, Hanna; Schwitulla, Judith; Dietzel-Drentwett, Svenja; Fasching, Peter; Beckmann, Matthias; Theuser, Anna-Katharin (Integrative Cancer Therapies, 2018)
PURPOSE: Although the demand from patients for integrative medicine is increasing, complementary medicine services are still quite heterogeneous and have not been incorporated into clinical routine. The aim of this study was to systematically evaluate improvements in side effects and quality of life associated with a hospital-based integrative medicine program in the modern breast cancer patient care setting. METHODS: In a cross-sectional study, integrative health counseling and treatment were evaluated in women with breast cancer. Over a 15-month period, data for 75 patients from an integrative medicine consultancy service with standardized operating procedures were collected at the University Breast Center for Franconia. At baseline, the patients answered a questionnaire on their medical history, symptoms, and the treatment goals they were hoping to achieve with integrative medicine. In the follow-up, patient-reported outcomes related to side effects of conventional cancer treatment and patients' quality of life were analyzed. RESULTS: Among 60 patients with the therapy goal of reducing the side effects of conventional treatment, 46 (76.7%) were successful. Among 57 patients hoping to improve disease-related quality of life, 46 (82%) reported success. Whereas patients with metastatic disease achieved a reduction in the side effects of conventional therapy, quality-of-life improvements were predominantly achieved by patients with a good treatment prognosis. CONCLUSIONS: Breast cancer patients benefit from the counseling and treatment provided with integrative medicine in all phases of tumor disease. Integrative treatment services should be included as part of patient care in clinical routine work to offer patients the maximum quality of care and safety with complementary therapies.
EVALuna2:209953

Skin irritability to sodium lauryl sulfate is associated with increased positive patch test reactions - Schwitulla, Judith; Brasch, J.; Löffler, H.; Schnuch, A.; Geier, J.; Uter, Wolfgang (British Journal of Dermatology, 2014)
As previous observations have indicated an inter-relationship between irritant and allergic skin reactions we analysed data of synchronous allergen and sodium lauryl sulfate (SLS) patch tests in terms of a relationship between SLS responsiveness and allergic patch test reactions.To analyse differences in terms of allergen-specific and overall reaction profiles between patients with vs. those without an irritant reaction to SLS.Clinical data of 26 879 patients patch tested from 2008 to 2011 by members of the Information Network of Departments of Dermatology were analysed. After descriptive analyses, including the MOAHLFA index, the positivity ratio and the reaction index, a negative binomial hurdle model was adopted to investigate the correlation between SLS reactivity and positive patch test reactions.Men, patients aged >= 40 years and patients with an occupational dermatitis background were over-represented in the SLS-reactive group. Patients with an irritant reaction to SLS showed a higher proportion of weak positive reactions, as well as more questionable and irritant reactions to contact allergens than patients not reactive to SLS. The risk of an additional positive patch test reaction increased by 22% for SLS-reactive patients compared with those who were SLS negative.The marked association between SLS reactivity and the number of positive reactions in patch test patients may be due to nonspecific increased skin reactivity at the moment of patch testing only. However, increased SLS reactivity could also be due to longer-lasting enhanced skin irritability, which may have promoted (poly-)sensitization. Further studies, for example with longitudinal data on patients repeatedly patch tested with SLS and contact allergens, are necessary.
EVALuna2:5456

Torsional osteotomies of the femur - Dickschas, Jörg; Harrer, Jörg; Reuter, Benoit; Schwitulla, Judith; Strecker, Wolf (Journal of Orthopaedic Research, 2015)
Various pathologies of the hip or knee, such as patellofemoral malalignment or femoroacetabular impingement may be caused by a femoral torsional deformity. When diagnosed and analyzed, it is treated by femoral torsional osteotomy. Thirty femoral torsional osteotomies in 25 patients were included, the principal symptoms were patellar dislocation in 15 patients, anterior knee pain in 17, and femoroacetabular impingement in two. A computed-tomography-based measurement of the torsional angle was performed in all patients. Japanese Knee Society score, Tegner activity score, Lysholm score, and visual analog scale score were determined before surgery and at follow-up after 41 (6-113) months. Femoral internal torsion was on average 40.9° (29° - 66°; normal 24°). Surgical treatment consisted of a femoral external torsional osteotomy of on average 13.8° (5° - 26°). Tegner activity score increased non-significantly (p-value 0.326) from 3.57 to 3.71. Japanese Knee Society score improved significantly from 72 to 87 (p-value 0.004) while Lysholm score rose significantly from 66 to 84 points (p-value 0.004). Pain relief was demonstrated by a significant decrease in the VAS score from 5.6 to 2.4 (p-value 0.007). No further patellar dislocation was reported. Torsional deformities of the femur frequently cause symptoms in the knee or hip joint. After thorough assessment and diagnostic investigation, a femoral external torsional osteotomy provides significant pain relief as well as patellofemoral stability. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???-???, 2015.
EVALuna2:5480

Treatment landscape of advanced breast cancer patients with hormone receptor positive HER2 negative tumors - Data from the German PRAEGNANT breast cancer registry - Hartkopf, Andreas D.; Huober, Jens; Volz, Bernhard; Nabieva, Naiba; Taran, Florin-Andrei; Schwitulla, Judith; Overkamp, Friedrich; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; et al. (BREAST, 2018)
PURPOSE: This study describes comprehensive data from a breast cancer registry concerning the use of endocrine treatment (ET) and chemotherapy in the first, second and higher therapy lines in hormone receptor (HR) positive, HER2 negative metastatic breast cancer (MBC). METHODS: The PRAEGNANT study is a real-time registry for patients with MBC. Therapies were categorized into the following categories: chemotherapy, aromatase inhibitor (AI), tamoxifen, fulvestrant, or everolimus plus ET and reported for first, second and third line or higher therapy use. Also treatment sequences for the first, second and third therapy line were analyzed. RESULTS: This analysis includes 958 patients with HR positive, HER2 negative MBC. 42.7% were treated with a chemotherapy in the first therapy line compared to 45.9% receiving an ET. A total of 25.9% were treated with everolimus plus anti-hormone therapy in any therapy line. 34.1% were treated with fulvestrant as single agent therapy. Analyzing therapy sequences, the administration of three different chemotherapies in a row was the most frequently used pattern. CONCLUSIONS: This analysis shows that across all three first therapy lines chemotherapy is a dominant therapy for HR positive, HER2 negative MBC patients. Education about the efficacy of ET might help to increase its use and decrease the possible burden of chemotherapy related toxicities.
EVALuna2:36436